A DFT study of methanol synthesis from CO2 hydrogenation on Cu/ZnO catalyst. (15th August 2023) - Wang, Xingzi; Zhang, Hai; Qin, Huang; Wu, Kunming; Wang, Kai; Ma, Junfang; Fan, Weidong
Highlights: The promoting effect of atom doping on CO2 methanolization over Cu/ZnO based catalyst is studied using DFT method. Cu-ZnO heterostructure improves the fromate pathway of CO2 hydrogenation by MSI (metal-support interaction). The scaling relationships between adsorption energies with the correlation coefficients R 2 ≈ 0.8 are extracted. The performance of various metal promoters is ranked as Al > Ga > Mg, Pt > Pd > Au. Abstract: The usage of CO2, a vital carbon source, is of great application value in carbon neutrality. Hydrogenation is one of the most promising approaches to convert the CO2 into high-value chemicals like methanol. The development of the hydrogenation of CO2 mainly lies in the design of safe and efficient catalysts. Focusing on the mechanism and the interface effects, the hydrogenation of CO2 to methanol over Cu/ZnO-based catalyst was investigated in this work. To study the enhancing effect of metal promoters, atomic doping was simulated on Cu/ZnO-X(Al, Mg, Ga, Pt, Pd, Au) catalyst. Based on the designed atomic doped mode, density functional theory (DFT) calculation was conducted to analyze the adsorption of intermediates, thermodynamic reaction path, and kinetics of CO2 methanolization. The results show that Cu-ZnO heterostructure improves the HCOO path of CO2 hydrogenation by metal-support interaction (MSI). A linear relationship between the adsorption energy of the intermediates via hydrogenation process was found with the correlation coefficient R 2 ≈ 0.8 . The order of the highest activation barriers for the overall reaction is Cu/ZnO-Au > Cu/ZnO-Mg > Cu/ZnO-Pd > Cu/ZnO-Pt > Cu/ZnO-Ga > Cu/ZnO > Cu/ZnO-Al. The diverse performance of various metal promoters was ranked as Al > Ga > Mg, Pt > Pd > Au. Our simulation work well corresponds the previous experimental results conducted by other scholars and will provide guidance for future design of the high-efficient catalysis for CO2 hydrogenation.